2009
DOI: 10.1002/dmrr.917
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of prevention: do participants of a type 2 diabetes prevention program experience increased mental distress?

Abstract: The interim analysis on mental health outcome of a type 2 diabetes prevention program comprising extensive phenotyping and risk assessment rules out adverse psychological effects, suggesting rather beneficial changes concerning symptoms of anxiety, depression and overall psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It revealed that after 9 months of lifestyle intervention on individuals without prior mental pathology, there was a significant reduction of mood disorders such as depression, anxiety, and distress. 68 The relationship between people's instinctive perception and the real risk of contracting cardiovascular disease was assessed in a Dutch cross-sectional study conducted using a questionnaire during medical consultations involving 490 patients between 40 and 70 years of age. 69 The recognition of the risk condition was most evident in smokers, hypertensive and obese patients than in diabetic patients.…”
Section: New Technological Approachesmentioning
confidence: 99%
“…It revealed that after 9 months of lifestyle intervention on individuals without prior mental pathology, there was a significant reduction of mood disorders such as depression, anxiety, and distress. 68 The relationship between people's instinctive perception and the real risk of contracting cardiovascular disease was assessed in a Dutch cross-sectional study conducted using a questionnaire during medical consultations involving 490 patients between 40 and 70 years of age. 69 The recognition of the risk condition was most evident in smokers, hypertensive and obese patients than in diabetic patients.…”
Section: New Technological Approachesmentioning
confidence: 99%
“…To our knowledge, no published study to date has examined the psychological effects of receiving a diagnosis of dysglycemia. However, after 9 months in a 24-month lifestyle intervention for T2DM prevention in a high-risk (with or without dysglycemia) German population, participation was not associated with higher levels of anxiety, depression, or overall psychological distress than in the general population (210).…”
Section: Effectiveness Of Screening For Hyperglycemia: Potential Benementioning
confidence: 77%
“… 27 Another trial showed that the implementation of a diabetes prevention program was associated with a decrease in depressive symptoms in the intervention group compared with the control group. 28 The authors of both trials suggest that decreased depressive symptoms may be related to a heightened sense of control over diabetes. 27 , 28 However, a meta-analysis of web-based interventions that promoted better diabetes care did not show that such interventions were associated with decreased depression.…”
Section: Discussionmentioning
confidence: 99%
“… 28 The authors of both trials suggest that decreased depressive symptoms may be related to a heightened sense of control over diabetes. 27 , 28 However, a meta-analysis of web-based interventions that promoted better diabetes care did not show that such interventions were associated with decreased depression. 29 …”
Section: Discussionmentioning
confidence: 99%